1991
DOI: 10.1128/jb.173.6.1873-1878.1991
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of maltodextrin-binding sites in LamB, an outer membrane protein from Escherichia coli

Abstract: We have directly measured the stoichiometry of maltodextrin-binding sites in LamB. Scatchard plots and computer fitting of flow dialysis (rate-of-dialysis) experiments clearly establish three independent binding sites per LamB trimer, with a dissociation constant of approximately 60 ,uM for maltoheptaose. The current model for LamB's function as a specific pore is discussed with respect to the symmetry in LamB's kinetic properties and the implications of our results.LamB (also called maltoporin) is a trimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Liposome swelling assays showed that maltoporin has a high permeation rate for maltose and maltodextrins, while uptake of sucrose could hardly be detected (Luckey and Nikaido, 1980). Maltodextrins up to maltoheptaose could be transported, as was shown in in vivo and in vitro uptake experiments with radiolabelled sugars (Gehring et al ., 1991; Charbit et al ., 1998). In contrast, uptake of sucrose is mediated by the plasmid‐borne sucrose regulon, which consists of the scrKYABR genes.…”
Section: Substrate‐specific Porinsmentioning
confidence: 56%
“…Liposome swelling assays showed that maltoporin has a high permeation rate for maltose and maltodextrins, while uptake of sucrose could hardly be detected (Luckey and Nikaido, 1980). Maltodextrins up to maltoheptaose could be transported, as was shown in in vivo and in vitro uptake experiments with radiolabelled sugars (Gehring et al ., 1991; Charbit et al ., 1998). In contrast, uptake of sucrose is mediated by the plasmid‐borne sucrose regulon, which consists of the scrKYABR genes.…”
Section: Substrate‐specific Porinsmentioning
confidence: 56%
“…Besides enzymes, two sugar transporters were induced at high pH, the maltose oligosaccharide porin MalB (4,17,36) and the galactose binding protein MglB (25). These transporters should be useful for uptake of the hydrolyzed glycogen and lactose in LBK.…”
Section: Discussionmentioning
confidence: 99%
“…channel conductance, which has occasionally been observed in noise experiments (Kolb and Bamberg, 1977). On the other hand, it is likely that the LamB trimers contain three identical channels (Ferenci and Lee, 1989;Gehring et al, 1991). Table 3 contains also the stability constants, K*, for maltopentaose binding derived from two parameters fits of So as a function of the maltopentaose concentration similar…”
Section: Estimation Of the Single-channel Conductance Of The Lamb Chamentioning
confidence: 99%
“…However, the most convincing reason for the small value of g is probably caused by the architecture of LamB in E. coli outer membrane. LamB is organized as trimers in the outer membrane (Palva and Westermann, 1979) and one trimer contains three channels surrounded by a ,3-sheet structure (Clement and Hofnung, 1981;Ferenci et al, 1988;Ferenci and Lee, 1989) and three binding sites for sugars (Gehring et al, 1991). Thus, it is very likely that in the single-channel records three channels are measured simultaneously (g = 150 pS), while the noise analysis recognises the single conductive unit (g = 50 pS).…”
Section: Maltopentaose Transportmentioning
confidence: 99%